Automatic Task Machine (ATM) Design for Logistic Package by Method Analytical Hierarchy Process (AHP) Through Approach the Design for Manufacturing (DFM) - Deni Pranata; Dodi Sofyan Arief (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2021)
The Automatic Task Machine (ATM) machine for logistics packages is a machine vision to measure the dimensions and other components in form load cell, which serves to measure the mass of an object. This machine design was development the addition of components such as insert card, screens, navigation buttons, receipt printers, automatic package doors and a storage room delivery mechanism. Method of Analytical Hierarchy Process (AHP) was chosen to determine the ATM design for the optimal logistics package for the best alternative decision. The questionnaires were made to get priority consumer needs, which it used for the initial design. The consumer needs questionnaire was based on several indicators, namely: ergonomics, measurement of dimensions and weight, package transmission and package storage. The next stage was selecting the optimal design using AHP, which involves Expert based on the indicator of a product. The highest indicator value obtained for the logistics package ATM is